Herbal Prescription, DSGOST, Prevents Cold-Induced RhoA Activation and Endothelin-1 Production in Endothelial Cells. (15th April 2014) - Cho, Sung-Gook; Go, Ho Yeon; Park, Jeong-Su; Jung, Ki-Yong; Sun, Seung-Ho; Choi, You-Kyung; Song, Yun-Kyung; Park, Jong-Hyeong; Jun, Chan-Yong; Ko, Seong Gyu
Abstract : Herbal prescription, Danggui-Sayuk-Ga-Osuyu-Saenggang-tang (DSGOST), has long been used to treat Raynaud's phenomenon (RP) in traditional Chinese medicine (TCM). However, a biological mechanism by which DSGOST ameliorates RP is yet deciphered. In this study, we demonstrate that DSGOST inhibits cold-induced activation of RhoA, in both vascular smooth muscle cells (VSMC) and endothelial cells (EC), and blocks endothelin-1-mediated paracrine path for cold response on vessels. While cold induced RhoA activity in both cell types, DSGOST pretreatment prevented cold-induced RhoA activation. DSGOST inhibition of cold-induced RhoA activation further blocked α 2c-adrenoreceptor translocation to the plasma membrane in VSMC. In addition, DSGOST inhibited endothelin-1-mediated RhoA activation and α 2c-adrenoreceptor translocation in VSMC. Meanwhile, DSGOST inhibited cold-induced or RhoA-dependent phosphorylation of FAK, SRC, and ERK. Consistently, DSGOST inhibited cold-induced endothelin-1 expression in EC. Therefore, DSGOST prevents cold-induced RhoA in EC and blocks endothelin-1-mediated paracrine path between EC and VSMC. In conclusion, our data suggest that DSGOST is beneficial for treating RP-like syndrome.